2008
DOI: 10.1017/s0033291707002541
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind and social inference in children and adolescents with bipolar disorder

Abstract: Consistent with past findings in adult bipolar disorder (BD), PBD youth performed more poorly than controls on ToM tasks. Data suggest that ToM ability may be more impaired in affectively charged contexts. Additionally, an earlier onset of illness among PBD youth may interfere with the development of social-cognitive skills. ToM disturbances may be a useful treatment target in PBD, with the aim of facilitating more accurate assessment of social cues and better interpersonal functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 63 publications
4
56
0
17
Order By: Relevance
“…The biases in affective information processing observed in BD have been linked with altered information processing speed and deficits in verbal memory and response inhibition (Schenkel et al 2008;Passarotti et al 2010;Singh et al 2010;Jacobs et al 2011;Passarotti et al 2013). In particular, previous studies in BD have consistently shown a robust effect of negative stimuli on cognitive processing Passarotti et al 2011;Pavuluri et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The biases in affective information processing observed in BD have been linked with altered information processing speed and deficits in verbal memory and response inhibition (Schenkel et al 2008;Passarotti et al 2010;Singh et al 2010;Jacobs et al 2011;Passarotti et al 2013). In particular, previous studies in BD have consistently shown a robust effect of negative stimuli on cognitive processing Passarotti et al 2011;Pavuluri et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Schenkel et al [79] found that young people with bipolar disorder showed Theory of Mind deficits, i.e. a reduced capacity to infer what others are thinking.…”
Section: Neurobiological Characteristicsmentioning
confidence: 99%
“…Fossati et al 2014;Ha et al 2013;Sharp et al 2011). Jugendliche mit bipolarer Störung lös-ten Theory-of-Mind-Aufgaben schlechter als gesunde Jugendliche; früher Krankheitsbeginn und manische Symptome wirkten sich hierbei zusätzlich negativ auf die Mentalisierungsfähigkeit aus (Schenkel et al 2008 …”
Section: Der Verlauf Psychischer Störung Von Adoleszenz Ins Erwachsenunclassified